Days of autonomy for optimal Battery Sizing in Stand-alone Photovoltaic Systems - Meriem Andam; Jamila El Alami; Younes Louartassi; Rabie Zine (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2023)
The main purpose of our article is to optimize the battery sizing by identifying the most appropriate number of autonomy days. A case study has been established and simulated to define the optimal number. In the others current researches, only a small importance has been attributed to the battery autonomy. The objective is generally to ensure a continuous presence of energy especially for isolated systems while this is not always optimal nor economical and does not necessarily guarantee a safe supply. Nevertheless, an over dimensioning of the battery will lead to a consequent cost and a loss of energy. The results show that the number of days of autonomy must correspond to the minimum ratio linking the lack of energy to the surplus during a specific period.